PIRAMIDA UMUR DAN PENGELOMPOKAN POPULASI IKAN BONTI-BONTI (Paratherina striata) SECARA SPASIAL DI DANAU TOWUTI, SULAWESI SELATAN - Syahroma Husni Nasution (BERITA BIOLOGI, 2011)
Bonti-bonti (Paratherina striata) is an endemiz and vulnerable fish in Lake Towuti and L. Mahalona. The fish population tend to decreasing due to intensive fishing and habitat quality decline. This study was aimed re reveal the age pyramids and the grouping of fish populations as a basis for describing condition and diversty of fish populations. The study was conducted in L.Towuti at five stations. Samples were collected using experimental gillnet with mesh sized ], ¾, 1, dan 1¼ inches. Meansurement of morphometric characters of  fish consist of 22 characters. Results shows that fish population at each station features a different age pyramid. at station inlent of L. Towuti and Loeha Island, the age pyramid type which is dominated by juveniles a reletively rapid population growth. At station Cape Bakara, outlet of lake Towuti and Beau, the age pyramid type tend to be mederate. This shows the fish population is dominated by medium-size, fish populations in stable condition. Obtained 12 characters that have a strong correlation values. ANCOVA test results showed no difference in morphometric characters between the stations in male and female. Based on ANCOVA test assumed that the Bonti-Bonti at fish station is a population group.